ANALISIS PERSEPSI MASYARAKAT TERHADAP KOMUNITAS PEDULI LUBANG JALANAN KOTA MALANG - Faizal Kurniawan (IKIP Budi Utomo Malang, 2017)
Malang City with all its facilities is ancrowded city. As a result the streets in most areas in Malang Raya is becoming frequently used. The density of vehicle volume every day resulted in many holes in the road. However, late handling of the municipal and district governments resulted in more and more potholes in the streets. Of course this results in disappointment for road users. Many victims of accidents caused by falling due to potholes. Not least the victims of this perforated road encourage a group of young people to form a Community Care for the Hole of the Road. This group moves voluntarily. Social counciosness encourages them to form this community. In the action, they make a circular sign or edge with a white pylox against the holes on each road segment. The goal is white as a sign for road users to see the white marka they have created. The sign is felt quite effective because in the distance before the hole, the rider can lower the speed. A lot of appreciation is given to this community. Because by remembering the many holes in the streets of Malang, and the number of “Personal Capital” they have spent for this social action. Their action also received a response from the mayor. This study uses a case study approach and indepth interview method to community members and also a source of road users who recognize the existence of this grassroots community. Observations are made to this community by following all the activities of this group. As a result, people’s perception of the two groups is divided into two, the pros and cons of their actions. In the contrary reasoned that the existence of sentences that are not appropriate to be displayed in public facilities. In conclusion, the pro-society perception towards grassroots movements can be a resistance movement for government policies that are slow to deal with this problem. Evidenced by the more intense they carry out the action, the response of the city government and Malang district faster. It is expected that this social awareness will encourage Malang city and district government to be more sensitive to the sound of netizens in both social media and aspirations directly.